2003
DOI: 10.4012/dmj.22.126
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adding Hydroxyapatite on the Flexural Strength of Glass Ionomer Cement

Abstract: This present study investigated the effects of the addition of hydroxyapatite (HA) on the flexural strength and microstructure of conventional GIC, and its effect on the cement's initial flexural strength at different storage conditions. Specimens were fabricated by mixing HA in whisker or granule form into commercially prepared GIC, and these were subjected to a threepoint bending test and SEM observations. Some specimens were stored in different conditions from dry to wet for 15 minutes to an hour prior to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…Commercially available Hydroxyapatite powder (SYBOGRAF TM ) was used in the study. Eight percent by weight of Hydroxyapatite powder was mixed with powder of conventional GIC and this Hydroxyapatite added cement was mixed with polyacrylic acid liquid of conventional GIC [6]. Sixty three test specimens were prepared as mentioned previously and stored in deionized water at 37 0 C.…”
Section: Preparation Of Test Specimenmentioning
confidence: 99%
“…Commercially available Hydroxyapatite powder (SYBOGRAF TM ) was used in the study. Eight percent by weight of Hydroxyapatite powder was mixed with powder of conventional GIC and this Hydroxyapatite added cement was mixed with polyacrylic acid liquid of conventional GIC [6]. Sixty three test specimens were prepared as mentioned previously and stored in deionized water at 37 0 C.…”
Section: Preparation Of Test Specimenmentioning
confidence: 99%
“…Arita 21) reported improved mechanical strength of GIC, in the absence of resins or fillers, by the addition of HAp whiskers. The addition of HAp granules also strengthened GIC, not by reinforcement but through chemical interactions with the cement matrix 22) . However, there has been no report to notice the powder characteristic of HAp in the improving properties of GIC by using HAp.…”
Section: Introductionmentioning
confidence: 99%
“…Cement mix was condensed into the mold and clamped for 10 min at room temperature, unclamped and maintained for 15 min (short-term test) or 50 min (long-term test 17) ) at 100% humidity at 37°C, and then stored in artificial saliva (Saliveht ® Aerosol, TEIJIN Ltd., Osaka, Japan) for 35 min (short-term test), or 23 h or 1 year (long-term tests). The samples for the flexural strength test were then subjected to a three-point bending test using a universal testing machine (AG-1kNX, Shimadzu Corp., Kyoto, Japan) at a crosshead speed of 0.5 mm/min.…”
Section: Mechanical Properties 1 Flexural Strength Testmentioning
confidence: 99%
“…In these approaches, the addition of substances as reinforcements to GIC did not compromise its fluoride release 14) or compressive strength 15) . Recent reports of the addition of hydroxyapatite (HAp) into commercially prepared GIC showed improvement in the cement's mechanical properties, i.e., compressive and flexural strength [16][17][18] with good bonding and fluoride properties 17,19) . Moreover, our previous study demonstrated that the addition of HAp particles with highly reactive properties, such as a high specific surface area, can enhance the mechanical and chemical properties of conventional GIC for dental restoration 20) .…”
Section: Introductionmentioning
confidence: 99%